Randomized clinical trial to change parental practices for drug use in a telehealth prevention program: a pilot study - Juliana Y. Valente; Tais Campos Moreira; Maristela Ferigolo; Helena M.T. Barros (Elsevier, 2019)
Objectives: Programs for parents have been found to have a direct positive impact on reducing the consumption of psychoactive substances by adolescents, as well as having an indirect impact on reducing risk factors and increasing protective factors. The present study aimed to verify if a telehealth prevention program based on a brief motivational intervention helps to reduce parental risk practices and increase parental protective practices for drug use in comparison with psychoeducation. Methods: A pilot randomized controlled trial was performed at the National Service of Guidance and Information on Drug Use (Ligue 132), from September 2014 to December 2015, with the parents of adolescents (n = 26). The outcome measures were parental style, risk, and protective parental practices. Results: The brief motivational intervention was found to be more effective than psychoeducation in reducing the negligent behavior of parents. Furthermore, when comparing pre- and post-intervention data, the brief motivational intervention helped to change parental style and the large majority of parental practices: increasing positive monitoring, as well as decreasing physical abuse, relaxed discipline, inconsistent punishment, and negative monitoring. Conclusions: These results demonstrate that the telehealth intervention is effective in modifying the parental practices known to help in preventing drug use. Studies with more number of subjects are required so that the results can be substantiated and generalized. Resumo: Objetivos: Os programas para pais parecem ter um impacto positivo direto sobre a redução do consumo de substâncias psicoativas por adolescentes, bem como um impacto indireto sobre a redução dos fatores de risco e aumento dos fatores protetores. O presente estudo visou a verificar se um programa telessaúde de prevenção com base em uma intervenção breve motivacional ajuda a reduzir as práticas de risco dos pais e aumentar as práticas protetoras com relação ao uso de drogas, em comparação à psicoeducação. Métodos: Um ensaio piloto controlado randomizado foi feito no Serviço Nacional de Informações e Orientações sobre Drogas (Ligue 132), de setembro de 2014 a dezembro de 2015, com os pais de adolescentes (n = 26). As medições dos resultados foram o estilo dos pais e as práticas de risco e protetoras dos pais. Resultados: A intervenção breve motivacional parece ser mais eficaz do que a psicoeducação na redução dos comportamentos negligentes dos pais. Adicionalmente, quando comparada aos dados pré e pós-intervenção, a intervenção breve motivacional ajudou a mudar o estilo dos pais e a grande maioria das práticas dos pais: aumentou o monitoramento positivo e reduziu o abuso físico, disciplina permissiva, punição não condizente e monitoramento negativo. Conclusões: Esses resultados demonstram que a intervenção telessaúde é eficaz na mudança das práticas dos pais, conhecida por ajudar a prevenir o uso de drogas. Estudos com maior número de indivíduos são necessários para que os resultados possam ser comprovados e generalizados. Keywords: Prevention, Adolescent, Drug use, Parent programs, Telehealth, Motivational intervention, Palavras-chave: Prevenção, Adolescente, Uso de drogas, Programa para pais, Telessaúde, Intervenção motivacional